KESALAHAN EJAAN DALAM SURAT DINAS SISWA KELAS VI SD - Sulasih Sulasih (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2018)
The purpose of this study were to describe the usage errors of spelling in formal letter of students grade VI SDN Cluring, District Kalitengah Lamongan. This study was designed to use a qualitative descriptive approach. This research data is the errors contained in the letter of the sixth grade students of SDN Cluring, District Kalitengah Lamongan, while the source of research data is a collection of letters that made the student. To collect the data, this study uses three techniques, namely technical documentation, refer to the technique, and technique noted.From the results of a study of sixth grade students of SDN letter Cluring, District Kalitengah Lamongan, there are some errors, which include errors in spelling, there are six errors in spelling, namely (1) improper use italics, (3) suffix errors word choice, (4) the error of writing a compound word, (5) writing errors of abbreviations and (6) the use of punctuation errors